2020
DOI: 10.1177/0007650320949845
|View full text |Cite
|
Sign up to set email alerts
|

Executive Migration Matters: The Transfer of CSR Profiles Across Organizations

Abstract: This study investigates whether and how the corporate social responsibility (CSR) profile of a company transfers to another company when an executive leaves a firm. We integrate upper echelon and institutional theories, and develop a novel measure of CSR profiles to explore this issue with a longitudinal data set of executive migrations over a 14-year period. We find that migrated executives assimilate elements of their old firms’ CSR profiles into their new firms (i.e., narrowing the distance between the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…In doing so, we provide a perspective that helps to reinforce the relationship between CSR and CEOs (Aguinis & Glavas, 2012; Chin et al, 2013; Frynas & Yamahaki, 2016; Saridakis et al, 2020). Thirdly, and in contrast to previous work (Kim et al, 2020; Oh et al, 2018), we focus on the characteristics of the CEO that drive the company's approach to CSR as opposed to those that hinder its development. Fourthly, since there may be multiple valid profiles that drive a company's CSR and since different combinations of attributes can achieve similar results, we contribute to the field by using a method that hitherto has seldom been employed, that of the fsQCA, which allows us to further the study and identification of the individual profiles of those who occupy the highest positions in management bodies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In doing so, we provide a perspective that helps to reinforce the relationship between CSR and CEOs (Aguinis & Glavas, 2012; Chin et al, 2013; Frynas & Yamahaki, 2016; Saridakis et al, 2020). Thirdly, and in contrast to previous work (Kim et al, 2020; Oh et al, 2018), we focus on the characteristics of the CEO that drive the company's approach to CSR as opposed to those that hinder its development. Fourthly, since there may be multiple valid profiles that drive a company's CSR and since different combinations of attributes can achieve similar results, we contribute to the field by using a method that hitherto has seldom been employed, that of the fsQCA, which allows us to further the study and identification of the individual profiles of those who occupy the highest positions in management bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, prior studies anchored in the principles of the upper echelon theory have shown that a firm's CEO exerts a significant impact on CSR (Carpenter et al, 2004; García‐Sánchez et al, 2020; Saridakis et al, 2020) and that the CEO's attributes provide a powerful explanation for the differences in CSR across companies (Chin et al, 2013; Tang et al, 2015). Indeed, Kim et al (2020) find that migrated executives incorporate CSR elements from their old firms into their new organisations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study by Zolotoy, O'Sullivan, Seo, and Veeraraghavan (2021) finds that a firm's CSI record enhances the positive relationship between group sentiment and corporate charitable giving. In addition, Kim, Moon, and Kim (2022) find that the migration of executives from firms with lower CSI scores enhances the level of assimilation between the two firms in terms of their CSI behavior.…”
Section: Path M2mentioning
confidence: 86%
“…Finally, a process perspective is needed to understand why CSI is allowed and institutionalized in firms and how and when it is transferred, as understanding these processes is necessary to prevent these behaviors from occurring. In this regard, Kim et al (2022) discovered evidence of the transfer of these behaviors to other firms when the CEO migrates, opening a relevant area for future research.…”
Section: Conclusion: What We Know and What We Need To Knowmentioning
confidence: 98%